2017
DOI: 10.5937/psihdan1702161k
|View full text |Cite
|
Sign up to set email alerts
|

First symptoms and support / aid to families children with disoerders of Autism spectrum

Abstract: Podizanje deteta sa poremećajem iz spektra autizma (PSA) predstavlja izazov koji zahteva značajnu uključenost svih članova porodice, informisanost porodice o karakteristikama poremećaja kao i o dostupnim vidovima zdravstvene zaštite i podrške roditeljima i deci. Cilj: Utvrđivanje koji su prvi simptomi, uzrast deteta kada je postavljena dijagnoza, utrvrđivanje dostupnosti dodatne pomoći iz domena obrazovanja i socijalne zaštite, kao i dodatne pomoći za roditelje dece sa PSA. Materijal i metode: Korišćen je meto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…The majority of the studies did not report specific types of disabilities, or their sample consisted of people with multiple disabilities or caregivers of individuals with multiple disabilities. Three studies focused on intellectual disabilities (Buljevac & Leutar, 2017;McConkey et al, 2013;Petrović et al, 2016), one included mothers of children with Prader-Willi syndrome (PWS) (Čagalj et al, 2018), one mothers of children with Williams syndrome (Milić Babić et al, 2017), three focused on autism spectrum disorder (ASD) (Daniels et al, 2017;Krsmanović et al, 2017;Pejovic Milovancevic et al, 2018), one included persons with visual impairments (Stanimirović et al, 2012), and two studies focused on physical disabilities (Karačić, 2012;Levačić & Leutar, 2011).…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of the studies did not report specific types of disabilities, or their sample consisted of people with multiple disabilities or caregivers of individuals with multiple disabilities. Three studies focused on intellectual disabilities (Buljevac & Leutar, 2017;McConkey et al, 2013;Petrović et al, 2016), one included mothers of children with Prader-Willi syndrome (PWS) (Čagalj et al, 2018), one mothers of children with Williams syndrome (Milić Babić et al, 2017), three focused on autism spectrum disorder (ASD) (Daniels et al, 2017;Krsmanović et al, 2017;Pejovic Milovancevic et al, 2018), one included persons with visual impairments (Stanimirović et al, 2012), and two studies focused on physical disabilities (Karačić, 2012;Levačić & Leutar, 2011).…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Our review showed that Croatian and Serbian caregivers of PWD received informational, emotional, practical, and financial support at different degrees. Informational support was depicted through information about rights, characteristics of disability, children's health needs, and available formal support (Čagalj et al, 2018;Daniels et al, 2017;Golubović et al, 2015;Krsmanović et al, 2017;Milić Babić et al, 2017;Stanimirović et al, 2012). The main sources of information were other caregivers of PWD, internet, and NGOs, followed by psychologists and teachers, while primary care physicians and social workers were mentioned less (Čagalj et al, 2018;Daniels et al, 2017;Golubović et al, 2015;Krsmanović et al, 2017;Lisak et al, 2017;Milić Babić et al, 2017;Pejovic Milovancevic et al, 2018).…”
Section: Types Of Support Reported By Caregiversmentioning
confidence: 99%
See 2 more Smart Citations
“…and this is a support measure that is applicable in the Republic of Serbia since 2012(Damjanović & ĐorĎić, 2014). Even though every child with diagnosis qualifies for shadow teachers services, according to Social services law of Republic of Serbia (2011), a previous research conducted in this country shows that only 12% of children with special educational needs have this type of service(Krsmanović et al, 2017), which is unfortunately not enough and there should be more services and organizations that can allow the children and their families to obtain the support they need (Vlaović-Vasiljević et al, 2016).…”
mentioning
confidence: 99%